KEAWETAN KAYU TUSAM (Pinus merkusii Jungh. et de Vr.) DAN MANGIUM (Acacia mangium Willd.) SETELAH FURFURILASI - Jamal Balfas; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Two regrowth wood species, i.e. tusam (Pinus merkusii Jungh. et de Vr.) and mangium (Acacia mangium Wild.) were used in this study. Specimens measuring 25 mm x 25 mm x 50 mm and 5 mm x 25 mm x 25 mm were prepared for testing against dry-wood termite (Cryptotermes) and subteranean termite (Coptotermes) respectively. All specimens were air-dried to approxi mately 16-18% moisture content. One group of the specimens was further oven - dried to reach moisture content of 6-8%. Furfurylation was carried out by soaking wood specimens for 24 hours in a 98% fuifuryl alcohol solution containing 0.35% (v/v) of ZnCl2 as catalyst. Furfurylated specimens were then cured at l000C for 48 hours. Control and treated specimens were exposed to dry-wood and subteranean termites for 12 and 4 weeks respectively.Treated specimens revealed a weight gains of 10 to 40 % depending on size of specimens and wood species. Speciesmens usd for testing drywood termites gained less weight than those of subteranean termites. Tusam specimens markedly showed a higher weight gain than mangium. Furfurylation using method 1 resulted in comparable weight gain to that of method 2. Control specimens of tusam an mangium are both encountered susceptible to dry-wood and subteranean termite attacts. Tusam had less initial durability against Coptotermes than mangium, but the wood species had a similar durability against Cryptotermess. The modified wood with furfuryl alcohol abviously possessed an improved durability upon the two termites. Tusam specimens gained more durability improvement than mangium.